Relação entre atenção compartilhada e operantes verbais em crianças com autismo - Oliveira, Sabrina David de (2022)
An early characteristic of Autism Spectrum Disorder (ASD) is the joint attention deficit, manifested by impairment in the pointing gesture, showing with the function of sharing interest with others or in the difficulty in following the pointing gesture or the indicating gaze from other people. Joint attention is considered a milestone in child development and a significant predictor for language. Knowledge about joint attention in ASD contributes to early diagnosis and intervention. The first chapter aimed, through a systematic review according to PRISMA, to analyze academic scientific productions on joint attention in children with ASD and to verify which instruments are most used to assess joint attention. The results showed that the instruments most used in combination or separately were: ESCS, ADOS and eye tracking. The second chapter carried out a systematic review with the objective of verifying the possibility of correlation presented in the scientific literature between joint attention and language in children with ASD. The results showed that there is a correlation between joint attention and language. Finally, the third chapter aimed to compare performance in joint attention contingencies with the level of development in echoic, mand, tact and intraverbal verbal operants. Ten children aged between 2 and 10 years old participated. A questionnaire adapted from the VB-MAPP and ESCS instruments was used to assess verbal operants (mand, tact, echoic and intraverbal) and joint attention. Spearman's Correlation Coefficient was used to analyze the correlations between them. In general, it was possible to observe a significant correlation between joint attention and verbal operants.